Study on slow-release mechanism of salt-storage anti-icing fog seal. (26th September 2022) - Zhu, Jie; Huang, Jiacong; Zhao, Qixiong; Ling, Lishan; Qin, Yue; Xi, Chenchen; Meng, Yongjun
Graphical abstract: Highlights: A pharmacokinetic equation is utilized to the release of anti-icing fog seal. Calcium acetate is conducted to prepare eco-friendly anti-icing emulsified asphalt. Release mechanism of anti-icing fog seal is related to temperature and geometry. Abstract: To expand the design ideas of the slow- and controlled-release performance of salt-storage anti-icing fog seals, this study first assumed a release environment based on the principles of drug release kinetics and then examined the influence of antifreeze content, temperature, and asphalt mixture surface structure on the release mechanism of antifreeze agents by fitting the results of the designed cumulative antifreeze release test for the anti-icing fog seal with the Peppas equation. The pharmacokinetic equation with the release mechanism parameters, K and n, effectively described the release mechanism of the antifreeze inside the fog seal. The antifreeze content did not affect the percentage rate of diffusion (diffusion mechanism) but was positively correlated with the mass release rate. Temperature was positively correlated with the release rate parameter K, and the surface structure of the asphalt mixture reduced the K and n values, which substantially improved the slow-release performance.